The Christianisation of Scandinavia: a comparative study - Sanmark, Alexandra (University of London, 2006)
The aim of this thesis is to examine the Christianization of Scandinavia, focusing on the methods of conversion employed by secular rulers and clerics. In order to achieve this aim, use will be made of comparative material from Anglo-Saxon England, Old Frisia, and Old Saxony. Conversion has been defined as the actions taken by secular rulers and/or clerics to achieve the Christianization of a society according to the contemporary norms of Christianity. The study will focus, in particular, on the 150 years after a secular ruler has taken charge over the spread of Christianity in these areas. The rulers are either internal or external to the kingdoms in question. The Scandinavian countries will thus be closely studied from c. 95o/iooo, Anglo-Saxon England from c. 597, and Old Frisia and Old Saxony from the end of the seventh century. This comparative approach has been chosen due to the scarcity of primary sources from Viking Age and early medieval Scandinavia. The material from England, Frisia, and Saxony has been employed as a `guide' to indicate what to search for in the Scandinavian sources. The primary sources that have been most commonly used, in all the geographical areas, are secular and ecclesiastical legislation. Many of these laws have hitherto been almost unexplored in the study of conversion. Archaeological evidence, such as excavated cult sites, burial grounds, and churches, has however also proven to be useful. The thesis focuses on a number of specific questions. These include: what are the requirements for successful conversion? What specific strategies were pursued by secular rulers and clerics? How did conversion affect the life of the wider population? Both forceful and more peaceful methods were used in conversion. What were the differences in the methods and their effects? What elements of pre- Christian religious custom and Christianity led to continuity or change after conversion?